Perceived Stress, Hope, and Health Outcomes Among Medical Staff in China During the COVID-19 Pandemic - Zhang, Xin; Zou, Rong; Liao, Xiaoxing; Bernardo, Allan B. I.; Du, Hongfei; Wang, Zhechen; Cheng, Yu; He, Yulong (Frontiers in Psychiatry, 2021)
This study investigated the buffering role of hope between perceived stress and health outcomes among front-line medical staff treating patients with suspected COVID-19 infection in Shenzhen, China. In the cross-sectional observational study with online questionnaires, medical staff's perceived stress, anxiety, depression, sleep quality, and hope were measured by the 10-item Chinese Perceived Stress Scale, Hospital Anxiety and Depression Scale, the Pittsburgh Sleep Quality Index, and the Locus-of-Hope Scale, respectively. A total of 319 eligible front-line medical staff participated. The prevalence of anxiety (29.70%), depression (28.80%), poor sleep quality (38.90%) indicated that a considerable proportion of medical staff experienced mood and sleep disturbances during the COVID-19 pandemic. Internal locus-of-hope significantly attenuated the effects of stress on anxiety, depression, and sleep quality.Moreover, external family locus-of-hope and external peer locus-of-hope significantly moderated the association between perceived stress and depression. The prevalence of symptoms indicate that both mental and physical health outcomes of front-line medical staff deserve more attention. Both internal and external locus-of-hope are significant protective factors for medical staffs' mental health and might be promising targets for intervention.